Socio-Economic Background and Computer Literacy of Postgraduate Students of Kuvempu University: A Study of Its Implications to Library Services - Ramakrishnegowda, K. C.; Walmiki, R. H. (Journal of Information and Knowledge, 2006)
Information Technology (IT) has brought rich dividends to the modern society. In the context of providing library and information services to users in higher education, the use of digital resources has become inevitable. This article reports the results of a questionnaire survey conducted to know the computer literacy existing among Postgraduate (PG) students at the time of their entry to various PG courses in Kuvempu University. The study has found that the socio-economic background of students such as domicile, caste category, gender, income group, religion and also the subject background have enormous impact on their take up and use of digital resources. The students belonging to the higher stratum of the society, economically rich, living in urban areas and those studying Science subjects are surpassingly ahead of their counterparts belonging to socially marginalised classes, economically poor, living in rural areas and also those studying in Social Sciences and Humanities. Suggestions have been put-forth to conduct training programmes and provide free access to IT-based services in the university libraries to the disadvantaged students.